ANALISIS STRATEGI BISNIS DENGAN MENGGUNAKAN PENDEKATAN METODE BALANCED SCORECARD PADA PT. XYZ - Ramelan, Satria Widyatama; Sidhi, Purnomo; Ardiansyah, Muhril (Journal of Business Strategy and Execution, 2009)
PT. XYZ established in 1986 by the idea of PT. B as the first foundry company in Indonesia and made a business partnership with PT. K who has access to the automotive spare part component technologies. To know and improve the company performance, therefore the research is held on PT.XYZ with balanced scorecard method. With the approach and result from the Balanced Scorecard method, there by, a strategic planning can be made for the company, so the company could analyze their performance with the external business condition, so the company can compete in automotive industry. The method used for this research is descriptive method with case study research. The qualitative data achieved by translating company vision and mission to be measureable and fit into the four balanced scorecard perspectives, then the quantitative data achieved by evaluating the financial ratios. For the research samples are 98 employees and 5 main customers of PT. XYZ. The result of balanced scorecard method is implemented to the SWOT analysis (Strength, Weakness, Opportunity, Threat), for strategic action. According to the SWOT analysis the company position in ST (Strength, Threat) zone, which is support the diversification strategies. The strategies might be useful by the company are concentric diversification, market penetration, and efficiency strategy. The IE matrix showed quadrant 1 for the company position, which mean that the company is in the growing position. With the applied strategies action, the company progress can be achieved and able to maintain the existence in the automotive industry.